La representación de la mujer en el cine ficción ecuatoriano, periodo 2011- 2021 - Ortiz Naranjo, Susana Gabriela (2024)
ABSTRACT: The research´s objective is to analyze the role of women in Ecuadorian fiction cinema, between the period 2011 to 2021, for this initially, seven winning Ecuadorian films of the "Kunturñawi" festival were taken as a sample, to establish said purpose, in the methodology, evaluation matrices were used, applying and developing the Bechdel, Uphold and Peirce tests, obtaining a negative result, due to the low participation of women in the films studied. As information support for the analysis, two renowned filmmakers were interviewed, Alfredo León, director of the films "Mono con Gallinas" and "Submergible", and the actress and director Mónica Mancero, creator of the film "Azules Turquesas", therefore, their answers differ from each other, which makes the discussion revolve around the stories shown on the screen. In the same way, the director of the "Kunturñawi" festival, Piedad Zurita, contributed with her point of view on the subject in question, reasons that allow us to clearly and concisely define the representation of the female gender in the film industry. The results obtained reflect the gender discrimination and lack of opportunities that women must face when entering the cinema, in the same way the vulnerability of their rights is exposed, inside and behind the cameras, although machismo has its origin in the culture, cinema serves as an instrument to change it, however, film productions in Ecuador do little to modify these paradigms. Keywords: Ecuadorian cinema, female gender, filmmaker, director, information, test, gender inequality.